2022
DOI: 10.1136/jitc-2021-003408
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrasound combined with nanobubbles promotes systemic anticancer immunity and augments anti-PD1 efficacy

Abstract: BackgroundThe poor immunogenicity of solid tumors limits the efficacy ofanti-programmed cell death protein 1 (anti-PD1)-based immune checkpoint blockade (ICB); thus, less than 30% of patients with cancer exhibit a response. Currently, there is still a lack of effective strategies for improving tumor immunogenicity.MethodsThe antitumor effect of ultrasound-stimulated nanobubbles (USNBs) alone and in combination with an anti-PD1 antibody was evaluated in RM1 (prostate cancer), MC38 (colon cancer) and B16 (melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Besides, the cavitation effect of ultrasound can also cause cell membrane cleavage and release of immunogenic DAMPs. Interestingly, it has been proved that ultrasonic cavitation can enhance the rate of ROS production and ICD induction ( 29 , 30 ). In recent years, several studies related to SDT have demonstrated that SDT induces immunogenic death of tumor cells as an “ in situ vaccine” that activates the body’s immune response against tumors and has been verified in vitro and in vivo ( 31 33 ).…”
Section: Main Mechanism Of Sdt Induction Icdmentioning
confidence: 99%
“…Besides, the cavitation effect of ultrasound can also cause cell membrane cleavage and release of immunogenic DAMPs. Interestingly, it has been proved that ultrasonic cavitation can enhance the rate of ROS production and ICD induction ( 29 , 30 ). In recent years, several studies related to SDT have demonstrated that SDT induces immunogenic death of tumor cells as an “ in situ vaccine” that activates the body’s immune response against tumors and has been verified in vitro and in vivo ( 31 33 ).…”
Section: Main Mechanism Of Sdt Induction Icdmentioning
confidence: 99%
“…[40,53] Although delivery mechanism of UTMD/UTND is gradually clarified, the impact of UTMD/UTND on tumor immune microenvironment is still unclear. A study [54] found that ultrasound-stimulated nanobubbles (USNBs) could elicit c-e) The populations of GZMB + CD8 + T, IFN-𝛾 + CD8 + T, and PD1 + Tim3 + CD8 + T cells in different groups. Adapted with permission.…”
Section: Direct Effect Of Utmd/utnd On Immune Responsementioning
confidence: 99%
“…Although delivery mechanism of UTMD/UTND is gradually clarified, the impact of UTMD/UTND on tumor immune microenvironment is still unclear. A study [ 54 ] found that ultrasound‐stimulated nanobubbles (USNBs) could elicit cavitation effect, and subsequently induce tumor cell lysis with DAMPs releasing. These DAMPs act as “eat me” signals to recruit antigen‐presenting cells (APCs) to present dead cell‐associated antigens to T cells, thereby promote adaptive antitumor immune response, showing great promise in the immunotherapy for cancer treatment ( Figure a).…”
Section: Ultrasound Targeted Micro‐/nanobubble Destructionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Hu et al (18), the authors compared the antitumor effect of ultrasound-stimulated nanobubbles alone and in combination with an anti-programmed cell death protein 1 (aPD-1) in RM1 (prostate cancer), MC38 (colon cancer), and B16 (melanoma) xenograft mouse models. They found that ultrasound-stimulated nanobubbles combined with aPD-1 induced tumor cell necrosis, significantly increased the release of DAMP and tumor antigen presentation, and promoted the invasion and antitumor activity of CD8+ T cells (Figure 3).…”
Section: Modulation Of Utmd On Tumor Immune Microenvironmentmentioning
confidence: 99%